Application of Video-Based Learning Media Using Videoscribe in Water Resources Development Lectures at Building Engineering Education FPTK UPI - Purwanto, Dedi; Sukadi, Sukadi; Rahayu, Sri (Jurnal Pendidikan Teknik Sipil, 2024)
Background: The learning process requires learning media components, one of which is to achieve the expected results. More interactive learning media was created to suit current conditions and accomplish this goal. In this case, the researcher designed and implemented a type of video-based learning media using the Videoscribe program in the Water Resources Development Course to increase students' understanding and mastery of Irrigation Buildings.Methods: The method used in this research is Research and Development (R&D) and uses the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development model. The subjects involved in this research were 3 experts for testing media aspects and independent aspects. The results of the validation by three experts obtained very good criteria. The research, it was carried out on students of the Class of 2020 Building Engineering Education Study Program FPTK UPI by holding an initial test, 3 treatment meetings, and a final test.Result: The research results show that: (1) The feasibility of Videoscribe learning media is included in the Very Good category. (2) There is an increase in student learning outcomes after being given treatment in terms of the average N-Gain value in the medium category.Conclusion: The feasibility of videoscribe media in the Water Resources Development Course can be said to be feasible to implement, seen from the learning outcomes, students experience increased learning outcomes.